(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The basic purpose of road location information management is to effectively manage and use the location of road and road facilities. From the viewpoint of the road manager, it is the main purpose to easily identify the location of the road facilities to be managed and to facilitate information transmission between the managers. For the driver who uses the road, it is easy to know his / her position on the road or on the road, and to transmit the positional information to each other easily and accurately when informing his / her own position. In addition, the system administrator who operates the road related system can easily and accurately update the data when the linearity of the road is changed or the extension is changed, or when the location of the managed road facility is changed. Especially, the road location information management system in the autonomous road transportation system is indispensable. Although it is easy to collect coordinate information based on the global geodetic system of GPS according to the spread of smart phones, it is difficult to intuitively recognize the position of the user expressed in numbers, and sharing or transmitting position information is not an effective method. Therefore, in this study, we analyze the characteristics of roads and discuss road location information management system that can satisfy road managers, road users, and system administrators at the same time.